Tasks and Principles of International Cooperation in the Field of Forensic Examination (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The basic categories: “tasks”, “principles”, “forensic examination”, “international cooperation” have been studied. The legal regulation of international cooperation in the field of forensic examination has been determined. The understanding of the category of “tasks and principles of international cooperation in the field of forensic examination” has been clarified.The task of international cooperation in the field of forensic examination has been defined as a set of legally established provisions aimed at ensuring effective and professional forensic examination in the course of international cooperation of forensic experts. The tasks of international cooperation in the field of forensic examination include the following: ensuring international cooperation between the subjects of forensic expertise, use of international qualified and objective expertise, providing assistance to international (foreign) forensic institutions (organizations), exchange of experience (training and retraining), providing international scientific support for the activities of forensic experts.The principles of international cooperation in the field of forensic examination have been defined as guiding (fundamental) principles and ideas laid down in the basis of international cooperation in the field of forensic examination and aimed at ensuring objective forensic activity. The following principles of international cooperation in the field of forensic examination have been formulated: good faith, freedom, equality, scientificity, international and legal clarity.It has been proved that the introduction of tasks and principles of international cooperation in the field of forensic examination into legal regulation of Ukraine is designed to be one of the driving changes in the legal basis for accelerating the integration of international forensic activity experience into the activity of domestic experts, implementation of new developments, Ukraine’s participation in developing programs in the field of forensic examination at the global level, including at the planning stage of the concept and strategy for developing forensic examination area.